2008
DOI: 10.1007/s00439-008-0584-7
|View full text |Cite
|
Sign up to set email alerts
|

A common haplotype of DRD3 affected by recent positive selection is associated with protection from schizophrenia

Abstract: The number and frequency of susceptibility alleles at loci associated to most psychiatric disorders is largely unknown, in spite of its relevance for the design of studies aiming to find these alleles. Both, common polymorphisms and rare mutations may contribute to the genetic susceptibility to complex psychiatric disorders, being the relative relevance of each type of variation currently under debate. Here, we confirmed the existence of a common protective haplotype against schizophrenia at the dopamine D(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…It is also possible that as yet undetected common or rare alleles confer risk for SZ, but were not genotyped in any of the populations. This possibility is supported by our haplotype based analyses at DRD3 and locus overlap observed with reports from other populations (Staddon et al, 2005; Dominguez et al, 2007; Costas et al, 2009). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is also possible that as yet undetected common or rare alleles confer risk for SZ, but were not genotyped in any of the populations. This possibility is supported by our haplotype based analyses at DRD3 and locus overlap observed with reports from other populations (Staddon et al, 2005; Dominguez et al, 2007; Costas et al, 2009). …”
Section: Discussionsupporting
confidence: 89%
“…Notably, nominally significant associations with haplotypes comprising rs2134655 & rs7631540 were also noted in our family sample set. Based on case-control analyses, Costas and colleagues recently proposed an operative positive selection for a common DRD3 haplotype in three independent schizophrenia samples of European origin (Costas et al., 2009). They also concluded that this particular “common but protective haplotype in Europeans” is at intermediate frequencies in other populations, being at the lowest in Sub-Saharan African populations.…”
Section: Discussionmentioning
confidence: 99%
“…In both CEU and YRI signatures, diverse disease categories such as cardiovascular, immunological, neurological, and skeletal and muscular diseases showed high associations (Table 2). This result attracted us because a number of individual studies have discovered population-specific loci susceptibility to, for example, cardiovascular diseases [10,22], schizophrenia [23], Crohn's disease [24-26] and diabetes [12,26,27], and have suggested they are consequences of natural selection. In addition, although the underlying mechanism has not been clarified, some previous genome-wide studies have reported an association between recent selection and the biological functions of skeletal development, brain development, and immune response [5,16].…”
Section: Resultsmentioning
confidence: 99%
“…Since YRI is more ''ancient'' than other populations and thus represents the ''ancestral'' one, the rising of the rs6280 T allele frequency in ASN and CEU supports the positive selection of rs6280 in these two populations. Costas et al [2009] suggested that a haplotype containing the derived allele Ser (T at the DNA level) at rs6280 has been under recent positive selection in European populations, leading to its fast increase in frequency, and that rs6280 is most probably the actual polymorphism subject to selection at this haplotype. However, unlike Costas et al [2009], we failed to find a significant selective sweep on DRD3 within ASN, possibly because of the limited sample size in our study or population stratifications across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Costas et al [2009] suggested that a haplotype containing the derived allele Ser (T at the DNA level) at rs6280 has been under recent positive selection in European populations, leading to its fast increase in frequency, and that rs6280 is most probably the actual polymorphism subject to selection at this haplotype. However, unlike Costas et al [2009], we failed to find a significant selective sweep on DRD3 within ASN, possibly because of the limited sample size in our study or population stratifications across studies. This work may just scratch the surface of natural selection on DRD3; such an endeavor should be enhanced by the generation of expanded data sets.…”
Section: Discussionmentioning
confidence: 99%